Attitudes in 2020 Towards Medical and Recreational Marijuana in Prohibitionist Nebraska. (January 2023) - Habecker, Patrick; Bevins, Rick A.
Despite considerable change in the legal status of marijuana in the United States in the 21st century, the state of Nebraska has become an outlier in maintaining a complete prohibition on the substance. We estimate overall public support for medical and recreational marijuana in the state of Nebraska. Our data comes from the 2020 Nebraska Annual Social Indicators Survey, an address-based sample of Nebraskan adults. We asked a question from the Pew Research Center if participants support legal marijuana for medical AND recreational use, medical use only, or if they think it should not be legal. We estimate that 83.18% of Nebraskans support medical marijuana legalization. There is less consistent support for legal recreational use than medical use alone. There are also associations between support preferences and age, political party, gender, and the amount of stigma a participant reports in their community towards people that use various substances.